PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF "MENATA” MENJELAJAH TATA SURYA UNTUK MENINGKATKAN PEMAHAMAN SISWA - Okeu Santika; Devi Afriyuni Yonanda; Irfan Nurhidayat (Edutainment : Jurnal Ilmu Pendidikan dan Kependidikan, 2026)
This study aims to develop an interactive learning multimedia entitled “MENATA Exploring the Solar System” to improve sixth-grade elementary students’ understanding of solar system concepts, including planet identification, sequencing, and characteristics. The research employed a Research and Development (R&D) approach using the ADDIE model with a one-group pretest–posttest design, involving 38 students. The multimedia integrates 3D animations, planetary exploration menus, QR-code access, and gamification features to enhance student engagement. Expert validation indicated a very high feasibility level (87.88%) in terms of content and design. Field testing results showed a significant improvement in students’ understanding, with mean scores increasing from 58.42 (pretest) to 86.58 (posttest), an N-gain of 0.67 (medium–high), and a significant t-test result (p < 0.001). Student responses also demonstrated high learning motivation (92%). The study concludes that the “MENATA” multimedia is effective in supporting science learning and strengthening science literacy in elementary education.